Evaluation of biomethane potential from by-products and agricultural residues co-digestion in southern Italy. (1st October 2018) - Valenti, Francesca; Porto, Simona M.C.; Selvaggi, Roberta; Pecorino, Biagio
Abstract: The suitability of the co-digestion of feedstock-mixtures (by-products and agricultural residues) depends on their ability to produce biogas. In this study, the effects of mixing five feedstocks (citrus pulp, olive pomace, poultry manure, Italian sainfoin silage and opuntia fresh cladodes) on anaerobic digestion for biogas production have been investigated by carrying out biomethane potential (BMP) tests on six different mixing ratios of the selected five biomasses. The BMP test results demonstrated that all the six studied feedstock-mixtures could be potentially used for renewable energy generation by biogas plants. More in detail, two mixing ratios of the studied feedstock-mixtures showed the best biomethane potential of 249.9 and 260.1 Nm 3 CH4 /tVS, respectively. Since this research study made it possible to screen the suitability and technical feasibility of the feedstock-mixtures analysed, the results provide the basis for subsequent pilot scale evaluation of anaerobic digestion in Mediterranean area, where by-products and agricultural residues are profuse and necessary to produce advanced biofuels. Highlights: A sustainable alternative to manage agricultural waste and by-products was proposed. Olive pomace and citrus pulp reuse for bioenergy could reduce environmental impacts. The co-digestion of different biomasses improves waste management sustainability. The technical feasibility of six FMs was evaluated by applying BMP testing approach. The selected FMs showed elevate potential to be used as feedstock for biogas plant.